Factors affecting for the usage of mobile applications among farmers in bulathsinhala area in sri lanka - Munasinghe, P.G.; Kanchanamala, H.D.C. (University of Jaffna, 2018)
Farmers invest much money for their cultivations but they failed recover their cost due to not having latest agricultural information. Mobile applications are maintained by local agencies to enhance information richness of farmers. However, the farmers do not use those applications. Therefore, the objective of this study was to investigate the factors affecting for the usage of mobile applications among farmers in agriculture in Bulathsinhala area. The administrative questionnaire was developed getting help from previous studies and data were collected from 100 respondents who had smart phones using purposive sampling technique. The respondents were farmers who engaged with Land, Mud and Animal farming. The results revealed that Education and Knowledge, Social & Family Factors and Economic Condition had a significance relationship with usage of mobile application. According to Pearson correlation, Facilitating Conditions is also statistically significant to use mobile application by farmers but using regression rejects it. Famers must be educated to use agricultural applications, as well as agricultural societies must share the cost of those applications.
Keywords: Agriculture; Economic Condition; Education and knowledge; Farmer; Mobile application